Comparison of Heffner Criteria and Light Criteria in Differentiating Exudative and Transudative Pleural Effusion - Devkota, Krishna Chandra; Hamal, S; Panta, PP (Nepal Medical College Journal, 2020)
Pleural effusion is present when there is >15ml of fluid is accumulated in the pleural space. It can be divided into two types; exudative and transudative pleural effusion. Tuberculosis and parapneumonic effusion are the common cause of exudative pleural effusion whereas heart failure accounts for most of the cases of transudative pleural effusion. This study was a hospital based cross sectional study performed at Nepal Medical College during the period of January 2016-December 2016. A total of 50 patients who fulfilled the inclusion criteria were enrolled. Pleural effusion was confirmed by clinical examination and radiology. After confirmation of pleural effusion, pleural fluid was aspirated and was analysed for protein, LDH, cholesterol. The Heffner criteria was compared with Light criteria to classify exudative or transudative pleural effusion. Among 50 patients, 30 were male and 20 were female. The mean age of patient was 45.4±21.85 years. The sensitivity and specificity of using Light criteria to detect the two type of pleural effusion was 100% and 90.9%, whereas using Heffner criteria was 94.87%, 100% respectively(P<0.01). There are variety of causes for development of pleural effusion and no one criteria is definite to differentiate between exudative or transudative effusion. In this study Light criteria was more sensitive whereas Heffner criteria was more specific to classify exudative pleural effusion. Hence a combination of criteria might be useful in case where there is difficulty to identify the cause of pleural effusion.